Differences in Technical Contact Performance Between Pool and Knockout Stages in Men's International Rugby Sevens - de Klerk, Stephanus (Division of Exercise Science and Sports Medicine, 2023)
Introduction: Rugby sevens is a high intensity, intermittent, collision field sport requiring a combination of physical fitness, and technical and tactical ability. Research on the running demands of rugby sevens matches has been synthesised to inform training and practice. In contrast, only a paucity of research is available on the technical contact demands. Moreover, less is known about the technical performances of successful teams. Therefore, the first part of this thesis conducted a systematic review of the literature of the tackle- and/or ruck frequencies within rugby sevens matches to understand the technical contact demands of rugby sevens. The second part of this thesis is an original study that retrospectively analysed and compared tackle and ruck events between the pool and knockout stages in one full season of the 2018/2019 International Men's Rugby Sevens World Series. Methods: For part one, a systematic search according to the PRISMA guidelines was performed on three electronic databases. The key word combinations included “Rugby Sevens” OR “Rugby” AND “Sevens” OR “Sevens” AND “Contact Demands”. The initial search across the databases retrieved 812 titles. The abstracts and full-text articles that presented with quantitative data on tackle- and/or ruck frequencies or rates within a given match or tournament were included. After the screening process, a total of 15 articles were included in the final review. For the second part of the thesis, all matches from the 2018/2019 International Men's Rugby Sevens World Series were analysed for tackle- and ruck events using Sports Code elite version 6.5.1. This equated to 21 226 tackle events and 6 345 rucks events across 450 matches. Results: The systematic review found that the mean rucks per match ranged from 7.1±4.6 (Mean±SD) to 9.5±4.5 for winning teams and 7.6±3.7 to 11.1±4.6 for losing teams on men's elite level. From a tackle demands perspective, studies on men's elite-level found that the mean tackles per match were 20.3±6.7 for winning teams and 20.4±6.1 for losing teams. In the original study, the mean tackles per match were 47.2, 95% CI 46.4-48.0 across the season with no significant difference between pool- and knockout stages of the tournaments. The mean rucks per match were 14.1, 95% CI 13.7-14.5 across the season with a significant difference between the stages of competition (P value < 0.001) (pool 14.8, 95% CI 14.2-15.4 vs knockout 13.3, 95% CI 12.7-13.9). Tackle variables that proved significant in pool matches for tackle outcomes included the type of tackle, point of body contact, tackle sequence, attacker intention, and match rank. For knockout matches only point of body contact and attacker intention proved to be significant Discussion: The systematic review provides a synthesis of the current state of technical contact demands in rugby sevens. The next step was to understand contact performance to identify what the determinants of contact success in rugby sevens are. For the original study, pool- and knockout stages had similar tackle frequencies, but dissimilar ruck frequencies, with more rucks occurring in the pool stages. Higher ranked teams and teams progressing to knockout stages of competition had less rucks and successful tackles. This showed that these teams were more proficient at evasive play with regards to contact performance. Practitioners and coaches can use this information to plan contact training and optimise tournament preparation in the Sevens World Series. The systematic review and original study gives insight into the contact demands and performance of a rugby sevens match. With stakeholder involvement this research has the potential to create innovative injury prevention and performance strategies to be implemented on all rugby sevens platforms.